Let Howard's age now equal x. Then, Tony's age now equals x+3. If five years ago the sum of their ages was 59, now the sum of their ages would be 59+10= 69 (each person has aged 5 years).
Then: 2x+3= 69
2x = 66
x = 33
33+3 = 36
So: Tony is 36 years old.
2007-01-30 16:54:01
·
answer #1
·
answered by Hagrid 3
·
0⤊
0⤋
Let the age of Howard be x years
therefore,the age of Tony is now x+3 years
Therefore,5 years back the age of Howard and Tony were x-5 and x+3-5 or x-2 years respectively
By the problem
x-5+x-2=59
=>2x-7=59
=>2x=66
=>x=66/2=33
There the present age of Howard is 33+3=36 years
2007-01-30 16:33:41
·
answer #2
·
answered by alpha 7
·
0⤊
0⤋
59 - 3 = 56 divided by 2 = 28 so 28 + 3 + 5 = 36 years old
2007-01-30 16:36:01
·
answer #3
·
answered by --------------- 2
·
0⤊
0⤋
Age now:
Howard: x
Tony: x + 3
Age 5 years ago:
Howard: x - 5
Tony: (x + 3) - 5
The sum of their ages 5 years ago was 59, so
(x - 5) + (x + 3) - 5 = 59
2x + -7 = 59
2x = 66, so
x = 33
Therefore,
Howard today is 33
Tony today is 33 + 3 = 36
2007-01-30 16:30:17
·
answer #4
·
answered by Puggy 7
·
1⤊
0⤋
let Tony's present age be X
(x - 5 - 3) + (x - 5) = 59
(x - 8) + (x - 5) = 59
x - 8 + x - 5 = 59
2x - 13 = 59
2x = 59 + 13
2x = 72
x = 72/2
x = 36
therefore, Tony's age is 36 years old
2007-01-30 16:38:53
·
answer #5
·
answered by wind_liao 2
·
0⤊
0⤋
Tony is 36.
2007-01-30 17:20:58
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
TONY IS NOW 36 YEARS OLD
2007-01-30 16:32:55
·
answer #7
·
answered by Steven H 5
·
0⤊
0⤋
Gay.
(36)
2007-01-30 16:28:50
·
answer #8
·
answered by Mr Jew-B-Cue 2
·
1⤊
0⤋
60 something?
terrible math.....
2007-01-30 16:30:37
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋